2006
DOI: 10.1007/s00253-005-0039-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct mating between diploid sake strains of Saccharomyces cerevisiae

Abstract: Various auxotrophic mutants of diploid heterothallic Japanese sake strains of Saccharomyces cerevisiae were utilized for selecting mating-competent diploid isolates. The auxotrophic mutants were exposed to ultraviolet (UV) irradiation and crossed with laboratory haploid tester strains carrying complementary auxotrophic markers. Zygotes were then selected on minimal medium. Sake strains exhibiting a MATa or MATalpha mating type were easily obtained at high frequency without prior sporulation, suggesting that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…As reported previously, compared to haploid strains, industrial polyploid strains, including diploid strains, have higher cell growth rates, cell yields, and tolerances to various stresses such as heat shock, hyperosmosis, high reactive oxygen species level, and inhibitor stress (Garay-Arroyo et al 2004;Hashimoto et al 2006;Higgins et al 2001;Martin and Jönsson 2003). Garay-Arroyo et al (2004) reported higher resistance of industrial strains to heat shock and to an oxidative environment than haploid laboratory strains.…”
Section: Discussionmentioning
confidence: 50%
“…As reported previously, compared to haploid strains, industrial polyploid strains, including diploid strains, have higher cell growth rates, cell yields, and tolerances to various stresses such as heat shock, hyperosmosis, high reactive oxygen species level, and inhibitor stress (Garay-Arroyo et al 2004;Hashimoto et al 2006;Higgins et al 2001;Martin and Jönsson 2003). Garay-Arroyo et al (2004) reported higher resistance of industrial strains to heat shock and to an oxidative environment than haploid laboratory strains.…”
Section: Discussionmentioning
confidence: 50%
“…Lane 3, 6, and 9 molecular weight marker; Lane 1 and 4 PC; Lane 7 SC; Lane 2, 5 and 8 Fhhh fragments were lost or recombined during the fusion process. It is well known that protoplast fusion in the same genus is feasible, and has been widely used in breeding of plants or microorganisms (Hashimoto et al 2006;John et al 2008). This technique may also be introduced to produce hybrids between taxonomically distant species (Xia et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto et al used UV irradiation to increase the frequency of LOH [16], and Whittaker et al used 12 kinds of chemicals to increase the frequency of chromosome loss [17]; however, these treatments are likely to randomly induce additional mutations and loss of other chromosomes. Because the purpose of yeast crossbreeding is to combine favorable traits of parental strains, these undesirable changes would be a concern for the resulting a- or α-type of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet (UV) irradiation of yeast diploid cells has been used successfully to increase the frequency of LOH to about 30% [16]. According to other report, chemicals such as benzonitrile and methyl ethyl ketone increase the frequency of chromosome loss [17]; however, these treatments have the potential to randomly induce undesirable mutations at loci other than the MAT locus or undesirable loss of chromosomes other than chromosome III, which might prevent the generated a- or α-type of cells from inheriting the desired properties of the parental strains when used in crossbreeding.…”
Section: Introductionmentioning
confidence: 99%